The Development of A School-Based Conflict Management Model in Aceh Besar Junior High School - Muchsin, Muchsin; Hambali, Hambali (SCAD Independent, 2019)
This paper aims to find out the causes of conflict in schools, how the style and techniques of conflict management, what are the approaches to conflict management in schools and the influence of schools on conflict-based management models at junior high schools in Greater Aceh. Conflict is a process expressed by two or more parties. Conflict affects all components of the school. Therefore, leaders and teachers must understand the management of conflicts that arise where they can have a positive impact on improving school quality. Furthermore, the authors want to develop a school model of conflict management based. This model is a resolution or stimulation technique to produce the desired resolution, especially in the development of schools based on conflict management models that are focused on producing instrument formulation. Based on the findings of the data, it was concluded that job satisfaction can be improved by increasing conflict management and teacher empowerment by the principal. The results of this study can also be useful for improving the quality of conflict management and teacher empowerment by principals to improve overall job satisfaction.